Eco-Friendly Isolation Of Colorant From Arjun Bark For Dyeing Of Bio-Mordanted Cotton Fabric: Short Title: Dyeing of bio-mordanted cotton with arjun bark colorant. Issue 12 (2nd December 2022) - Adeel, Shahid; Rehman, Fazal-ur-; Khosa, Muhammad Kaleem; Rajab, Shabana; Zia, Khalid Mahmood; Zuber, Mohammad; Batool, Fatima
ABSTRACT: The worldwide demand has been raised to use natural dyes in all applied fields of life due to their environmental-friendly and therapeutic nature. For the current study microwave rays as an eco-friendly extraction tool has been used to explore the natural coloring potency of Arjun bark for cotton dyeing. Arjun bark powder was exposed to microwave irradiation for up-to 5 min and was used for extraction of colorant in different media. It has been found that 50 mL of acidified methanol-solubilized extract obtained from 5 min microwave-treated powder has given excellent results when employed onto MW treated cotton at 55°C for 75 min, salt of Fe as chemical mordant and extracts of acacia and turmeric as bio-mordants employed at optimum condition has shown good to the excellent fastness ratings at grey scales. It is concluded that microwave treatment has good potential for the extraction of the colorant from Arjun bark for cotton dyeing and the application of sustainable mordants has made the process more aesthetic and sustainable.